Pelaksanaan Agenda Reforma Agraria Awal Masa Orde Baru (1967-1973) - Aprianto, Tri Chandra (History Department, Faculty of Humanities, University of Jember, 2021)
Agrarian Reform as a way to well organize of agrarian resources that is more fair, is the foundation of national economic development in many countries, including Indonesia. In Indonesia, Agrarian Reform has experienced ups and downs and crosses every political order. In the implementation also depends on the authorities. The New Order was of course different from the previous one, which was oriented to economic growth supported by foreign capital. As a result, the land needs to be arrangement of administration to support economic growth. This paper reconstruct the implementation of agrarian reform during the early days of the New Order (1967-1973), both ideologically, in its policy structure and in its technical implementation. The historical method is a necessity as the basis for writing it.